Teen Guide - Chamberlain, Valerie M.; Jones, Jan Perry, 1942-; Budinger, Peyton Bailey, 1939-; Brinkley, Jeanne Hayden (New York : Webster Division/McGraw-Hill, 1982)
A textbook dealing with relationships, family, home, decision-making and consumerism, clothing, and food.
Fourth ed. by J. H. Brinkley, published under title: Teen guide to homemaking.
Includes index.
Keywords: Home economics -- Juvenile literature; Home economics